2017
DOI: 10.1038/s41598-017-12747-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in cell-penetrating peptide transfection model

Abstract: Cell-penetrating peptides (CPPs) uptake mechanism is still in need of more clarification to have a better understanding of their action in the mediation of oligonucleotide transfection. In this study, the effect on early events (1 h treatment) in transfection by PepFect14 (PF14), with or without oligonucleotide cargo on gene expression, in HeLa cells, have been investigated. The RNA expression profile was characterized by RNA sequencing and confirmed by qPCR analysis. The gene regulations were then related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Furthermore, the neurophilin receptor is reported to internalize cationic peptides that have a K/RXXR/K C-terminal motif [28]. In one of our recent studies [29], we also demonstrated the involvement of autophagy signaling pathways in the uptake of PF14:ON and more particularly a differential regulation of several cell-surface receptors were found when the cells were treated with our complex. Among those receptors can be found connective tissue growth factor (CTGF), low-density lipoprotein receptor (LDLR) or β-adrenergic receptor 2 (ADRB2).…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, the neurophilin receptor is reported to internalize cationic peptides that have a K/RXXR/K C-terminal motif [28]. In one of our recent studies [29], we also demonstrated the involvement of autophagy signaling pathways in the uptake of PF14:ON and more particularly a differential regulation of several cell-surface receptors were found when the cells were treated with our complex. Among those receptors can be found connective tissue growth factor (CTGF), low-density lipoprotein receptor (LDLR) or β-adrenergic receptor 2 (ADRB2).…”
Section: Introductionsupporting
confidence: 66%
“…We have also shown that the use of agonists or antagonists to these receptors could modulate the efficiency of the delivery of SCOs in complex with PepFect14. [29] To find out new receptors involvement in the uptake of complexes or nanoparticles, the use of ligand interfering is widely used. The principle is to incubate cells with a drug that modulates a specific protein and to measure the efficiency of delivery depending on the concentration of the ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, anionic CPPs have also been shown to deliver fluorophores into a range of cell lines [9][10][11]. It should be noted that in many cases a finite window exists between a CPPs ability to translocate in the absence of cell toxicity and its more global effects on cells in the form of induction of plasma membrane porosity or other indirect effects [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…SRs have also been implicated in the uptake of spontaneously forming amphipathic CPP-PMO micelles, with SR knockout models having significantly reduced splice-switching activity in diaphragm and heart tissues compared to wild-type controls [ 84 ]. In an elegant study to further understand and identify uptake mechanisms of CPPs, RNA expression profiling of the early cellular response was performed in HeLa cells transfected with PepFect14 with or without an oligonucleotide cargo [ 85 ]. IPA analysis suggested that the autophagy pathway was being induced upon transfection and to validate this, ligands that modulate autophagy were coadministered with PF14-SSO in a HeLa luciferase splice-switching reporter system.…”
Section: Mechanism Of Cpp Mediated Uptakementioning
confidence: 99%